Cost-Effectiveness Analysis of Taxane-Based and Anthracycline-Based Chemotherapy in Stage 4 Breast Cancer Patients at Dr. Soetomo General Hospital, Surabaya, Indonesia - Adele Sabrina; Abdul Khairul Rizki Purba; Azril Okta Ardhiansyah; Annette d’Arqom (Universitas Airlangga, 2026)
Highlights: Epirubicin (anthracycline-based) showed the highest cost-effectiveness. Taxane-based regimens were less cost-effective compared with anthracyclines. Abstract Introduction: Breast cancer, particularly stage 4, contributes significantly to global morbidity and mortality. Anthracycline- and taxane-based chemotherapies are commonly used for metastatic breast cancer, but their high costs necessitate a cost-effectiveness analysis to inform healthcare financing. This study aimed to assess the cost-effectiveness of these therapies for patients with stage 4 breast cancer at Dr. Soetomo General Hospital, Surabaya. Methods: A retrospective review of medical records from 124 stage 4 breast cancer patients treated in inpatient and outpatient settings was conducted. Effectiveness rates and cost data for epirubicin, doxorubicin, docetaxel, and paclitaxel were analyzed. Data processing involved basic calculations in Google Sheets, and the average cost-effectiveness ratio (ACER) and incremental cost-effectiveness ratio (ICER) were calculated. Ethical clearance was obtained. Results: Epirubicin was the most cost-effective, with an ACER of 958,878 Indonesian Rupiah (IDR) and an ICER of -IDR 2,603,667. Conclusion: Epirubicin is the most cost-effective chemotherapy option for stage 4 breast cancer, supporting its use in resource-limited settings and guiding cancer therapy decisions.